Perception Of Illegal Migration And Sex Trafficking In Europe Among Younger Women Of Oredo Lga, Edo State, Nigeria: The Social Work And Ethical Considerations - OKAFOR, NNEKA IFEOMA; IWUAGWU, ANTHONY OBINNA; GOBO, BLESSING NGOWARI; NGWU, CHRISTOPHER NDUBUISI; OBI-KEGUNA, CHRISTY NGOZI; NWATU, UCHE LOUISA; RAHMAN, FARAH NAZ (Advances in Social Sciences Research Journal, 2020)
The movement of human populations across the planet has characterized human societies throughout history. However, the increasing rate of such movements across National borders has been in such a way that violates the immigration laws of the destination country, put trafficked persons at risk and has given birth to modern day slavery. This study was therefore designed to ascertain the perception of illegal migration and sex trafficking in Europe among young women in Oredo, Benin City, Nigeria. The study used a multi stage random sample of 90 women aged 18-40 years whom were interviewed using in-depth interviews (20) and Focus Group Discussions guides (7). The qualitative data generated were content analyzed and the results indicate that majority of the women perceive illegal migration and sex trafficking in Europe negatively. They however would not discourage anyone who wishes to engage in the act, partly due to the socio economic benefits derived therein. Given that illegal migration and sex trafficking in Europe is inimical to human and societal well-being, it therefore becomes necessary for social workers and ethical practitioners to advocate the formulation of policies and programmes focusing on ethical migration practice and women empowerment with aim to rehabilitate and reduce human sex exploitation.